Analysis of Initial Bubble Acceleration Using the Level-Set Method. (September 2015) - Dominik, M.; Cassel, K. W.
A new axisymmetric level-set code for incompressible, multiphase flows using the vorticity-streamfunction formulation has been developed. The level-set method is well suited to treating multiphase flows having complex interface shapes that may undergo topological changes, such as merging and splitting of bubbles. The initial acceleration of a single air bub- ble in water has been analyzed and found to be approximately 3.3 g, not 2 g, which is the predicted value from an added mass analysis based on potential-flow theory.